A Review of Immunotherapeutic Strategies in Canine Malignant Melanoma - Ramón M. Almela; Agustina Ansón (Veterinary Sciences, 2019)
In dogs, melanomas are relatively common tumors and the most common form of oral malignancy. Biological behavior is highly variable, usually aggressive, and frequently metastatic, with reported survival times of three months for oral or mucosal melanomas in advanced disease stages. Classical clinical management remains challenging; thus, novel and more efficacious treatment strategies are needed. Evidence-based medicine supports the role of the immune system to treat neoplastic diseases. Besides, immunotherapy offers the possibility of a precise medicinal approach to treat cancer. In recent years, multiple immunotherapeutic strategies have been developed, and are now recognized as a pillar of treatment. In addition, dogs represent a good model for translational medicine purposes. This review will cover the most relevant immunotherapeutic strategies for the treatment of canine malignant melanoma, divided among five different categories, namely, monoclonal antibodies, nonspecific immunotherapy activated by bacteria, vaccines, gene therapy, and lymphokine-activated killer cell therapy.